O serviço de manutenção da qualidade de água e o pagamento por serviços ambientais para Unidades de Conservação no Brasil - Andre Aroeira Pacheco (2015)
The natural capital provides numerous services to society, notably in the Protected Areas (PAs), which has been poorly recognized and valued. This study presents for the first time the monetary value of water quality maintenance by the Serra do Cipo National Park (SCNP). SCNP is well known for its water quality and abundance. The replacement cost method was used to valuate water provisioning by this national park. We found an average of R$ 36.18 million/year for the ecosystem service between 2012 and 2014. Such value has application in payment for ecosystem services (PES) programs, in the measurement of charges for water use and in compensation to SCNP. It also demonstrates the importance of PAs in providing clean water to society and help to raise environmental awareness. The value obtained is 30 times higher than the SCNPs budget and therefore highlights the economic benefits of conservation investment. Brazilian PAs have been constrained by a limited budget, as there is an immediate deficit of at least R$ 8.7 billion, plus a lag of about R$ 400 million/year for the responsible agency. A solution to this problem is proposed based on a PES program that could raise funds to be invested in Brazilian CUs and increase the recognition of its importance for human welfare and economic activities in Brazil. The proposal was adapted from successful programs in other countries used for conservation on private land, and it is the first wide PES proposed for PAs. The PES would serve all PAs through a National Fund and its budget would be raised on charging ten environmental services that were chosen because they are already established in ordinary economic transactions. Theycould work as an umbrella, ensuring the delivery of numerous other ecosystem services by PACs. Simulated scenarios of three of this services demonstrate potential revenues that could solve the outstanding debts, facing directly, quickly and definitively the PAs budget crisis.